Functional foods in genomic medicine: a review of fermented papaya preparation research progress - Marotta, F.; Catanzaro, R.; Yadav, et al., H. (Acta Biomedica Atenei Parmensis, 2012)
“Functional Foods” represent an emerging opportunity and they will certainly play a consistent and important role in future too. Such a new perspective entirely depends on the growing attention paid by nutritionists to the development of new innovating solutions aiming at acting on organic systems as well as on more general topics relating to consumer good health conditions. Differently from the past, when mainly retrospective epidemiological studies or empirical experiences were carried out on single nutrients, such a new and growing interest by the scientific community follows research deeply oriented to clinics supplemented by an accurate study on nutrients, genomics and single nutritional requirement diagnostics. Already in 1993, the leading journal Nature published a report “Japan is exploring limits between food and medicine” (Swinbanks 1993). Clearly the success of “Functional Foods” depends on the food industry capacity too of developing new effective products which on the one side meet any consumer request and on the other must be have positive effects on health, supported and validated by scientific research and therefore far beyond simple positive properties, as recently underlined in a meeting, organised by a no profit non governmental international association.